Immunoreactivity of transforming growth factor alpha in the normal adult gastrointestinal tract. Issue 5 (May 1992) - Thomas, D M; Nasim, M M; Gullick, W J; Alison, M R
Abstract : The immunolocalisation of transforming growth factor alpha (TGF alpha) in the normal human oesophagus and the gastrointestinal tract was elucidated using two different antibodies - Ab2, a monoclonal antibody reacting with part of the human TGF alpha molecule, and 26T a rabbit affinity purified polyclonal antibody raised against part of the rat TGF alpha peptide. There have been conflicting reports on the distribution of this growth factor in the gut. The results clearly showed that this peptide regulatory factor is confined to the luminal surface and foveolae in the stomach, restricted to the villous epithelium in the small intestine, and in the colon was seen in the upper one third of the crypt. This pattern indicates that the distribution of this peptide regulatory factor is within the differentiated compartment and indicates a role in differentiation besides its well known proliferative effects.